Revision of Charaea (Coleoptera: Chrysomelidae: Galerucinae) from Taiwan - Bezděk, Jan; Lee, Chi-Feng (Zootaxa, 2014)
Eleven species of the genus Charaea Baly, 1878 are recorded for Taiwan. These are illustrated and a key to the species is provided. Three species, Ch. houjayi sp. nov., Ch. maxbarclayi sp. nov. and Ch. haruoi sp. nov., are described and compared with similar species. Charaea kelloggi (Gressitt & Kimoto, 1963) is reported from Taiwan for the first time. Colour photos of habitus and drawings of both male and female genitalia are presented.